USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING HUMANITIES - Vaisov Azad (Western European Studies, 2024)
This article highlights the importance and benefits of using modern, innovative and interactive technologies in humanities lessons, as well as the effectiveness of using modern teaching methods necessary for their study
Keywords: History; creative thinking; innovation; interactive technology